2002
DOI: 10.1007/bf02412144
|View full text |Cite
|
Sign up to set email alerts
|

Rigid biological composite materials: Structural examples for biomimetic design

Abstract: ABSTRACT--Biological hard tissues are composites of inorganics and biopolymers, and, therefore, represent hybrid systems. The inorganic components may be oxides (e.g., SiO2, Fe304), carbonates (e.g., CaCO3) sulfides (e.g., FeS, CdS), or others, mostly in crystalline forms but also occasionally in glassy forms. The biopolymer is often proteinaceous, but can also involve lipids and especially polysaccharides (e.g., chitin). These hybrid materials can be found in single celled organisms (such as bacteria and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(55 citation statements)
references
References 14 publications
1
52
0
2
Order By: Relevance
“…Previous studies have also shown structural correlates between composite materials and physical properties in various biological systems, including bacteria, molluscs, vertebrates and insects (Hepburn and Chandler, 1976;Lin et al, 2009;Mayer and Sarikaya, 2002;Sun et al, 2008;Williams and Kramer, 2010). It thus seems likely that the distinct physical properties within the flagellum's cuticle might correlate with its unique physical properties, combining stiffness with flexibility and controllability.…”
Section: Histology Of the Flagellummentioning
confidence: 96%
“…Previous studies have also shown structural correlates between composite materials and physical properties in various biological systems, including bacteria, molluscs, vertebrates and insects (Hepburn and Chandler, 1976;Lin et al, 2009;Mayer and Sarikaya, 2002;Sun et al, 2008;Williams and Kramer, 2010). It thus seems likely that the distinct physical properties within the flagellum's cuticle might correlate with its unique physical properties, combining stiffness with flexibility and controllability.…”
Section: Histology Of the Flagellummentioning
confidence: 96%
“…These differences result in the exocuticle being both harder and stiffer than the endocuticle [133,137,[140][141][142]. As the exocuticle increases in hardness toward the interface with the endocuticle, there is an [161], (e) [158] (f) [215]. abrupt change in both hardness and stiffness of more than an order of magnitude between these two layers [137].…”
Section: Crustacean Exoskeletonsmentioning
confidence: 99%
“…However, nacre, through its "brick and mortar" composite structure of micronscale tablets and sub-micron scale adhesive protein-rich layers, enables outstanding mechanical performance including an excellent combination of stiffness, strength, impact resistance, and toughness (Curry, 1977;Weiner and Traub, 1984;Jackson et al, 1988). The ability of nacre to optimize mechanical performance by properly organizing materials at different length scales has attracted a large interest in developing biomimetic materials (e.g., He et al, 1997;Mayer and Sarikaya, 2002), which, in turn, necessitates a deep understanding of the biological mechanisms responsible for its superior properties.…”
Section: Prismatic Layermentioning
confidence: 99%